Thermal Decomposition of Lubricating Oil Under an Inert Atmosphere - Nejjar, K.; Zeriouh, A.; Zakarya, E.M.; Belkbir, L.; Hamad, M. (Asian Journal of Chemistry, 2011)
Weight losses in the thermal degradation of SAE 40 oil have been studied by means of dynamic experiments, carried out under nitrogen atmosphere. At slow heating rates the thermal decomposition phenomenon becomes very lucid. Furthermore, oil in use becomes thermally unstable and loses progressively its initial lubricant power also volatile organic fraction become affected by the ageing when the number of working hours of engine is increasing.